Regional Fiscal Policy and Provincial Fiscal Performance in Indonesia: The Dual Moderating Role of Fiscal Decentralization - Niko Silitonga; Harya Widiputra; Fangky Antoneus Sorongan (Yayasan Ilomata, 2026)
Fiscal decentralization has been widely implemented to improve regional fiscal efficiency and strengthen local fiscal capacity. However, empirical evidence regarding its effectiveness remains inconclusive, particularly in developing countries with diverse institutional capacities. This study examines the associations between regional fiscal policy instruments and provincial fiscal performance in Indonesia, proxied by the growth of Locally Generated Revenue (PAD), while investigating the moderating role of fiscal decentralization. Unlike previous studies that examine fiscal instruments separately or focus mainly on macroeconomic outcomes, this research develops an integrated framework that evaluates financing allocation, development expenditure, transfer funds, and other legitimate revenues within a moderated panel-data model. Using panel data from 33 provincial governments during 2017–2024, the study applies a fixed-effects regression model with interaction terms. The results show that development expenditure is positively and significantly associated with provincial fiscal performance, indicating that productive public spending strengthens regional fiscal capacity. In contrast, financing allocation and transfer funds show no significant direct associations with fiscal performance. Other legitimate revenues demonstrate a positive but limited association. Fiscal decentralization plays a dual moderating role by strengthening the association between transfer funds and fiscal performance while weakening the effects of development expenditure and other legitimate revenues. These findings suggest that the effectiveness of fiscal decentralization depends on fiscal instruments and local institutional capacity rather than producing uniform outcomes. This study contributes to the fiscal decentralization literature by providing an interaction-based empirical framework and practical evidence to support more effective decentralization policies and improve provincial fiscal performance in Indonesia.